2015
DOI: 10.1590/1980-5497201500010019
|View full text |Cite
|
Sign up to set email alerts
|

Redução das desigualdades no uso de consultas médicas no Brasil: análise das regiões Nordeste e Sudeste entre 2003 e 2008

Abstract: ABSTRACT:Objective: To analyze the socioeconomic inequalities in medical visits (MV) in the past year in Brazil. Methods: Data from adults aged ≥ 20 years old who participated in the Brazilian National Household Surveys and living in the Northeastern (2003; n = 75,652 and 2008, n = 79,779) and Southeastern (2003; n = 76,029 and 2008; n = 79,356) regions were analyzed according to MV. We compared MVs according to demographic and health variables in the first (D1) and last (D10) per capita family income decil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
3
0
3
Order By: Relevance
“…Já em relação ao uso dos serviços médicos, essas desigualdades educacionais aumentaram ao longo dos anos. Resultado diferente mostrando redução das desigualdades entre os mais ricos e os mais pobres na utilização de consultas médicas foi registrado entre as regiões Nordeste e Sudeste 23 . É importante ressaltar que as variáveis de renda e educação utilizadas para medir desigualdades são diferentes, apesar de que a educação pode ser considerada como uma proxy para renda.…”
Section: Discussionunclassified
“…Já em relação ao uso dos serviços médicos, essas desigualdades educacionais aumentaram ao longo dos anos. Resultado diferente mostrando redução das desigualdades entre os mais ricos e os mais pobres na utilização de consultas médicas foi registrado entre as regiões Nordeste e Sudeste 23 . É importante ressaltar que as variáveis de renda e educação utilizadas para medir desigualdades são diferentes, apesar de que a educação pode ser considerada como uma proxy para renda.…”
Section: Discussionunclassified
“…Another study with PNAD data from 2003 and 2008 found that women consulted doctors more than men. It also showed that women over 50, with higher income and higher self-reported morbidity, also consulted doctors more often 5 .…”
Section: Introductionmentioning
confidence: 95%
“…Studies that evaluated access to health services evidenced advances after the Sanitary Reform movement and SUS 3 5 implementation. Between 1981 and 2008, the number of individuals using primary care increased by approximately 450% 1 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Factors indicated to explain why adults and elderly people do not consult with physicians include the following: being male, less educated and family income. 8,9 A meta-analysis conducted in 2017 found that medical consultation frequency in the last year was 71%. 10 Other national studies with adults found similar results for having had a medical consultation in the last year, ranging between 64.8% and 74.2%.…”
Section: Introductionmentioning
confidence: 99%